Effect of platinum and pre-oxidation on the hot corrosion behavior of aluminide coating with NaCl at 1050 °C. (4th November 2020) - Peng, Jubo; Huang, Taihong; Song, Peng; Huang, Wenlang; He, Yang; Ma, Tao; Yang, Bixiao; Liang, Yuwei; Wu, Minxuan; Chen, Rong
Abstract: The hot corrosion behaviors of the aluminide coatings with different treatments on the surface of Ni-based alloy at high temperature were investigated. The aluminide coating modified by three different methods (pretreatment, Pt-modification and both), and then all the specimens were oxidized in lab air with NaCl salt at 1050 °C. During cycle oxidation, oxide scales on the surface of the aluminide coatings presented different morphologies, composition and corrosion behaviors. The oxide scale on the surface of the as-received aluminide coating without any treatments showed a poor dense and a bad adherence. However, the oxide scale on the surface of the aluminide coating with both Pt-modification and pre-oxidation exhibited the best hot corrosion resistance. In the NaCl corrosion environment, different treatments resulted in different corrosion mechanisms. Without any treatments, the oxide scale with NaCl at high temperature occurred internal active oxidation, which could promote the corrosion process and form the pores in the oxide scale. The internal active oxidation also presented in the oxide scale on the surface of the aluminide coating with pre-oxidation.